The evolution of operational art from Napoleon to the present - Olsen, John Andreas, 1968-; Van Creveld, Martin, 1946- (Oxford : Oxford University Press, 2011)
Based on country specific case-studies, 'The Evolution of Operational Art' describes how the concepts that underpin operational art originated, how they received practical expression in various campaigns, and how they developed over time.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Operational art (Military science) -- History; Operational art (Military science) -- History -- Case studies